Funding Scheme Options for Climate Change Mitigation in Forestry Sector - Fitri Nurfatriani; Dodik Ridho Nurrochmat; Mimi Salminah (Jurnal Ilmu Kehutanan)
Climate change mitigation actions significantly require strong financial support. One of the climate change financing schemes stated on the government regulation no 46/2017 is transaction of environmental services. The implementation schemes in the site level however have not been clearly explored yet. This paper explores funding scheme options for various forest management purposes in order to support climate change mitigation actions in forestry sector. Tanjung Jabung Timur District that is actively reducing emission from forest is chosen as the research location. The research shows environmental service funding schemes that could be implemented in Tanjung Jabung Timur are including Payment of Environmental Services (PES), Liability Rule (LR), and Purchasing Development Right (PDR). PES is effective to encourage forest management purposed for carbon stock; LR is to support carbon sequestration activities, while PDR is potential to support forest management for reducing carbon emission.